2007
DOI: 10.1080/00016480600740563
|View full text |Cite
|
Sign up to set email alerts
|

High frequency immittance for neonates: a normative study

Abstract: Conclusion. High frequency immittance measurements demonstrate promise in clarifying middle ear status for neonates but age-and gender-specific norms should be consulted. Objective. To describe high frequency immittance measurements using a 1000 Hz probe tone for a sample of 278 neonatal ears (0-4 weeks of age) in order to compile normative tympanometric and acoustic reflex criteria. Subjects and methods. Assessment of neonatal ears included 1000 Hz probe tone immittance measurements (tympanograms and ipsilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
6
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 22 publications
10
50
6
7
Order By: Relevance
“…The occurrence of acoustic reflex at 50, 55, or 60 dB was higher with the 1,000 Hz probe. Lower ASRTs were also found (10,21,22) and were justified by the small size of the external auditory canal of newborns by vibration of the wall of the canal after a sound stimulus. However, it is worth to mention that the minimum intensity for the analysis of AR in the equipment is 50 dB NPS.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The occurrence of acoustic reflex at 50, 55, or 60 dB was higher with the 1,000 Hz probe. Lower ASRTs were also found (10,21,22) and were justified by the small size of the external auditory canal of newborns by vibration of the wall of the canal after a sound stimulus. However, it is worth to mention that the minimum intensity for the analysis of AR in the equipment is 50 dB NPS.…”
Section: Discussionmentioning
confidence: 91%
“…With the 1,000 Hz probe, the average was 74.2 dB for the 1,000 Hz frequency and 62.9 dB for 2,000 Hz (Table 1). A study (21) found a mean of 93 dB for the 1,000 Hz and two other studies (10,22) found means of 73.05 and 76.2 dB for 1,000 and 2,000 Hz, respectively. In the these studies, no other frequencies were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(19,20,26,28) Como visto na análise das demais variáveis, apenas um estudo(19) utilizando a frequência de 678Hz foi encontrado, indicando valores próximos aos aqui descritos. Na frequência de 1000Hz diversos estudos apresentaram valores de Ymt próximos aos descritos (12,15,25). O estudo mais recente encontrado foi de MAZLAN(41), que ao avaliarem neonatos, encontraram média de Ymt igual a 1,06mmho.…”
Section: Discussionunclassified
“…A avaliação adequada das condições da orelha média no período neonatal resulta em encaminhamentos adequados à equipe médica e audiológica, podendo levar à melhora da eficácia dos programas de triagem auditiva neonatal (15).…”
Section: Introductionunclassified